Native orchid species of Garo Hills, Meghalaya - Momin, Kalkame Ch.; Kumar, Sunil (Indian Horticulture, 2020)
Orchid is one of the largest flowering plant families and the most complex having about 17,000 species all over the world and more than 1,000 in India. Of these, nearly 850 species are found in North East India. Meghalaya is a storehouse of richly variable and colourful orchids with as many as 325 species, which grow all over the Khasi, Jaintia and Garo Hills in the meadows, hillslopes and swamps, even on the wayside. Orchids are found in Meghalaya growing at different heights, mostly on trees, on mossy rocks and also on the ground. Jowai, Jarain, Tuber, Mukhaialong, Narpuh, and Raliang in east and west Jaintia hill districts and Tura peak, Nokrek, Baghmara and Rongrenggre in the Garo hills are some of the undisturbed areas providing habitat for wild orchids in Meghalaya. Meghalaya is well known for the exquisite flowering lady’s slipper orchids. Tura peak has many species, of which the Dendrobium densiflorum and Dendrobium chrysanthum are most common.